Valuation activity of Public Institutions in northeastern Lavalle (Mendoza, Argentina), according to goat producers = Valoración de la actividad de las Instituciones Públicas en el Noreste de Lavalle (Mendoza, Argentina), según los productores del sector caprino - Dayenoff, Patricio Mario; Schiarrone, C.; Accorinti, C.; Morales, M.; Pizarro Castaño, Juan Manuel (2018)
The objective of this research was to know how the goat producer perceives the public institutions linked to rural development processes of arid of La Asunción, Lavalle Department, Mendoza Northeast, Argentina. For this, a descriptive - exploratory study of cross cutting was developed, through a survey of 29 producers of a total of 40 residents. The public entities analyzed were: Dirección de Ganadería, CONICET, INTA Lavalle, Lavalle Municipality, Secretaría de Agricultura Familiar and Universidad Nacional de Cuyo. The survey results showed the INTA Lavalle as the best known entity in the area (92.9% of the producers), followed by the Municipality and the Secretariat with 75.86%. As for the institutional participation in specific goat production advice, the Dirección de Ganadería is that of higher participation with talks and specific meetings in the goat theme, covering the 38.52% of participation, followed by the Secretariat (21.26% ), and Lavalle Municipality (16.09%) and being the most appropriate themes feeding (25,29%) and facilities (16.67%). As for the institution acceptance, the Municipality showed the highest producers accordance with 48.28%, being the foundation, the subsidy provisions and tools without refund, added to that the institution is in constant contact with the population and in many cases, producer relatives works in it. It is stresses that 10.34% of the producers showed dissatisfaction with all. In the case of Dirección de Ganadería , the acceptance was only 3.45%, being the producers justification that is an organism that requires the loans refund, which does not provide subsidies, controls the animals moving, requires own register of marks and signals, is responsible for mandatory vaccinations, among others